SPATIAL VARIATIONS IN THE SIMILARITY OF EARTHQUAKE POPULATIONS: THE CASE OF THE 1997 COLFIORITO-SELLANO (NORTHERN APENNINES, ITALY) SEISMIC SEQUENCE - Alberti M. (My University, 2006)
The spatial properties of events in the 1997 Colfiorito-Sellano seismic sequence (Northern Apennines, Italy) were investigated using coherence, a parameter derived from seismic moment tensors that quantifies the kinematic similarity between focal mechanisms. The 1997 Colfiorito-Sellano seismic sequence predominantly consists of normal faulting earthquakes, with a few strike-slip and reverse faulting episodes. This kinematic heterogeneity is possibly related to the contemporaneous activity of two different sets of faults: NW-SE normal faults and NNE-SSW sub-vertical faults, the latter inherited from the previous Miocene compressional phase. The study used two independently-derived data sets of the same seismic sequence characterized by a different number of events and by different precision of spatial localisation. Their statistical significances, assessed through a reshuffling procedure, reveal that data sets with at least some hundreds of events and good positional precision are required to obtain significant results through coherence analysis. Results from the better quality data set indicate that this seismic sequence is characterized by a rapid decrease in the kinematic similarity between earthquake pairs within 2 km of separation, particularly along directions sub-perpendicular to the normal fault strike. The decrease rate seems to be controlled by the geometric characteristics of the normal faults, given that the mean along-dip distance between fault segments is 2 km. In proximity to pre-existing tectonic lineaments the relative abundance of strike-slip and reverse faults tends to decrease the kinematic similarity between events but does not influence the coherence decrease rate. The presence of mixed focal mechanisms (normal, reverse and strike-slip) in a single seismic phase implies that mixed fault types are not restricted to polyphase tectonic histories: such heterogeneous kinematics during a single phase may be induced by the presence of inherited discontinuities. © 2006 Elsevier B.V. All rights reserved.
Keywords: 1997 COLFIORITO-SELLANO SEISMIC SEQUENCE; COHERENCE; EARTHQUAKE POPULATION; SPATIAL ANALYSIS; Miocene; Cenozoic::Neogene::Miocene; Кайнозой::Неоген::Миоцен